2020
DOI: 10.3390/su12093920
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Parental Educational Level on Physical Activity in Schoolchildren

Abstract: The factors influencing physical activity participation in children are varied, although there is evidence that the educational level of parents may be one important factor. The aim of this study is to analyze the influence of parental education on the level of physical activity and the sedentary behavior of their children. The parents of 727 students, separated based on school group (preschool: n = 179; primary: n = 284; secondary: n = 230; high: n = 34), were invited to complete a series of questionnaires as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
4
23
1
2
Order By: Relevance
“…Surprisingly, cluster 2 with high education-parental level and majority boys, reported significantly greater levels of sedentary time and the most sedentary behaviors than all other cluster groups (except cluster 1). This finding is not in line with some other research, which has highlighted that both higher parental education level and boys are more likely to be related to greater levels of PA and reduced sedentary activities [ 12 , 30 , 37 , 55 ]. One explanation may be that by this age, children’s priorities shift towards educational pursuits such as homework, which is routinely more sedentary in nature.…”
Section: Discussioncontrasting
confidence: 92%
“…Surprisingly, cluster 2 with high education-parental level and majority boys, reported significantly greater levels of sedentary time and the most sedentary behaviors than all other cluster groups (except cluster 1). This finding is not in line with some other research, which has highlighted that both higher parental education level and boys are more likely to be related to greater levels of PA and reduced sedentary activities [ 12 , 30 , 37 , 55 ]. One explanation may be that by this age, children’s priorities shift towards educational pursuits such as homework, which is routinely more sedentary in nature.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings validated López-Bueno's warning about the potential health risks for children from socio-economically disadvantaged families. 42 Although studies have reported that parents with higher education levels tend to encourage their children to lead healthier lifestyles and engage in higher levels of PA, 53 , 61 previous literature reviews have shown a negative association between higher maternal, rather than parental, education level and children's PA, 62 typically in countries with lower economic status. 63 , 64 The studies in this review do not provide a clear argument for the influence of parental educational background.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be that the assessment of the neighborhood to be activity friendly is an indicator of higher family SES or higher educational levels of the parents. The result could be that parents with higher educational levels (living in presumably more activity friendly neighborhoods) place more value on educational aspects (doing homework) which might lead to more ST at home as was initially observed (Muñoz-Galiano et al, 2020). Previous studies reported an association between parental education level and achievement-oriented behavior (e.g., high reading frequency) of the child.…”
Section: Discussionmentioning
confidence: 79%
“…The highest educational level of both parents was used as the indicator for the SES of the included families. This was included as it is deemed the strongest socio-economic predictor of health or health behaviors in different contexts (Winkleby et al, 1992 ; Härkönen et al, 2018 ) including physical activity and SB (Loyen et al, 2016 ; Muñoz-Galiano et al, 2020 ), highest educational level of both parents was classified by the International Standard Classification of Education (ISCED) 2011 (United Nations Educational, Scientific and Cultural Organization, 2016 ). In accordance with previous studies (Hebestreit et al, 2016 ), ISCED levels zero to two have been defined as low, levels three and four as middle and levels five to eight as high SES (variable labels: low = 1, middle/high = 0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation